Pengaruh Motivasi dan Literasi Perpajakan terhadap Minat Mahasiswa Menjadi Konsultan Pajak dengan Growth Mindset sebagai Moderasi - Ni Putu Meisintha Ananda Saputri; I Nyoman Gede Arya Diatmika (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effects of motivation and tax literacy on accounting students’ interest in pursuing a career as a tax consultant, with growth mindset as a moderating variable. The study is motivated by inconsistencies in prior findings and the need to better understand the cognitive and psychological factors underlying students’ career interests. A quantitative approach was employed using a survey method by distributing questionnaires to undergraduate accounting students from six universities in Denpasar City. Purposive sampling was applied, yielding 368 respondents. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The results show that tax literacy and motivation have positive and significant effects on students’ interest in becoming tax consultants. Furthermore, growth mindset significantly moderates the effect of motivation on students’ interest, but does not moderate the effect of tax literacy on students’ interest. These findings indicate that tax knowledge is sufficiently strong to directly shape interest, whereas growth mindset primarily strengthens students’ motivational drive. Theoretically, this study supports the Theory of Planned Behavior (TPB) by demonstrating that cognitive and psychological factors play an important role in shaping career intentions. Practically, the findings are expected to inform universities in designing learning strategies and career development initiatives in the field of taxation.